Values and Livelihood Adaptation for Wetland Management and Climate Change: Lesson Learns from Kiat Ngong and Phapho villages, Beung Kiat Ngong Ramsar, Lao PDR - Somvilay Chanthalounnavong; Khamla Inkhavilay; Phansamai Phommexay (Indonesian Journal of Limnology, 2024)
Wetlands play a crucial role in community livelihood and water security management. The study was conducted in Kiat Ngong and Phapho villages inside the Beung Kiat Ngong (BKN) wetland Ramsar site, in the Pathounphone district, Champasack province. By gathering data from GIS, remote sensing, and ground study for referent and social-economic situations with communities. Farmers from two villages heavily rely on natural biodiversity resources from BKN for consumption and income. By looking at land use types, it shows farmers have paddy and crop fields inside and surrounding Ramsar sites, more than 16% of the catchment area. The majority size is broadleaf evergreen and deciduous forests at 24.9% and 24.3%, with 11.69% claimed as fallow land and located inside Xe Pain NPA. Recently, sources of income have varied, from livestock, rice, fish, cassava, and labor. People earn from aquatic resources an average of 300-400 US dollars/year. Since 2020, cassava has become a main source of income, especially for rich families. Then cassava has expanded quickly to fallow lands inside NPAs, but not yet intends to turn paddy into cassava. Agricultural activities rely solely on surface water. About 70% of paddy areas use water from wetland and rainfall; 20% of households use water from wells and rain; and 10% of people buy purified water from private companies for drinking and cooking. The experiment game to learn how people plan and manage their land and water needs shows that rich families (9% of the population in two villages) are well managed and looking for the alternative crop to grow and thinking of pumping up groundwater for gardening and rice fields, but petrol cost is a concern. While poor families (19% of the population in two villages) are lacking land, they only think of raising cattle and exchanging labor for a living. Collecting golden apple snails for sale becomes a good choice for family income.